2022
DOI: 10.3389/fmed.2022.847817
|View full text |Cite
|
Sign up to set email alerts
|

Contrast Sensitivity Is Associated With Chorioretinal Thickness and Vascular Density of Eyes in Simple Early-Stage High Myopia

Abstract: ObjectiveTo evaluate the contrast sensitivity function (CSF), chorioretinal thickness and vascular density as well as their relationships in subjects with simple early-stage high myopia.MethodsEighty-one young subjects were enrolled in this study. They were categorized into the simple high myopia group (sHM, n = 51) and the low-moderate myopia group (control group, n = 30). Monocular CSF under best correction was measured with the qCSF method. Retinal superficial and deep vascular density, inner and outer reti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…Zaben et al [31] reported a study to estimate the association between choroidal thickness in the macular area and retinal sensitivity in eyes with high myopia. And they found that retinal sensitivity in highly myopic eyes is directly correlated with choroidal thickness and does not seem to be associated with retinal thickness [10,[31][32] . All these findings are consistent with current study.…”
Section: Resultsmentioning
confidence: 99%
“…Zaben et al [31] reported a study to estimate the association between choroidal thickness in the macular area and retinal sensitivity in eyes with high myopia. And they found that retinal sensitivity in highly myopic eyes is directly correlated with choroidal thickness and does not seem to be associated with retinal thickness [10,[31][32] . All these findings are consistent with current study.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we found that retinal vessel density could be related to CSF. Liu et al (15) also found the correlation between CSF and the changes of high myopia fundus. For high myopia, loss of contrast sensitivity at higher spatial frequencies was observed, which may be due to retinal function disturbances, which may occur at an early stage even before the onset of retinal pathological events (14).…”
Section: Influence Factors Odds Ratio (95% Ci) P-valuementioning
confidence: 87%
“…Previous studies have found that the visual quality decreases in patients with high myopia ( 14 ). We hypothesized that the reduced CSF in myopic patients is related to changes in fundus structure, and there are only a few studies that have discussed the correlation between visual quality and retinal vessel density in young myopes ( 11 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous papers have reported that decreased CSF is correlated with retinal structural and microvascular alterations in patients with high myopia [ 30 ], diabetic retinopathy [ 9 ] and glaucoma [ 31 ]. To investigate the potential factors that may be associated with the CSF change in TAO patients, we also evaluated the retinal microvasculature and structure around the macula by OCTA.…”
Section: Discussionmentioning
confidence: 99%